Atividade de Pleurotus ostreatus, Pleurotus florida e Pleurotus djamor em larvas e adultos de Lucilia cuprina - Santi, Eduarda Maria Trentin (2021)
Lucilia cuprina, Diptera, Calliphoridae, has great importance due to being a disease vector for humans and animals, having global distribution and its infestation in sheep can result in loss and reduction of wool quality and death. The use on pesticides is the way to control these diptera, however, with the growing insect resistance to several of the active principles used, these treatments are becoming ineffective and the impact of excessive use of these products can cause loss to human and animal health and environmental imbalance. In light of this, studies have been performed using natural products from plants, algae and fungi in the control of these insects. The mushrooms of the Pleurotus genus are available in a wide variety of colors and species that present potentially medicinal bio-active compounds, with anti-parasitic action. Due to the potential of using fungi in pathogen control, this study aimed to verify the action of the Pleurotus genus, an edible mushroom, in the control of the Lucilia cuprina fly. The effects of aqueous extracts (AE) of the Pleurotus ostreatus, Pleurotus djamor and Pleurotus florida fungi were evaluated in Lucilia cuprina larvae and adults. In the larvae immersion tests, the P. florida AE was the only one that presented larvicide activity against L. cuprina, with EC50 of 11.42 mg/ml. In the assay with flies, where the spraying technique was applied with 1ml of each extract solution in 30 adult insects, all AE presented adulticide activity in all concentrations, P. ostreatus presenting the best results, with mortality between 75.86 and 100%. The chemical analysis of the aqueous extracts indicated the presence of tridecanoic acid, tetradecanoic acid, linolenic acid, 9,15 octadecadienoic acid and oxalic acid in the P. ostreatus AE, the presence of tridecanoic acid, linolenic acid, undecanoic acid, tetradecanoic acid and oxalic acid in the P. djamor AE and, in P. florida, none of these compounds was found. Our results showed an important larvicide effect of P. florida and adulticide effect of all aqueous extracts, highlighting P. ostreatus. However, more research is needed to establish the activity of Pleurotus on L. cuprina.